DUAL EDUCATION AT GERMAN UNIVERSITIES (Innovative professional education, 2025)
The article analyses the results of surveys of German university students studying in a dual form of education. The authors have found that in Germany young people choose dual education based on economic and academic motivation. The authors emphasise the need to create and consolidate links between the different priorities of stakeholders – the university, the social partner and the student
Keywords: dual learning, social partnership, students, universities, education, Germany